Study on Stress and Quality of life of people with Moderate Disabilities - 김영란; 김정현 (International Journal of Advanced Culture Technology(IJACT), 2024)
This study was conducted to explore the relationship between stress and the quality of life experienced by people with disabilities and to provide essential data for improving their quality of life and promoting their health. The data collection period was from November 2023 to January 2024. Fifty questionnaires were distributed, and 48 copies were used, excluding unfaithful responses. As a result of the study, since people with moderate disabilities show hesitancy in all of their daily life processes, not only physical rehabilitation but also psychological rehabilitation should be necessary so that they can accept their bodies that have turned into disabilities. In addition, programs for the acceptance of disabilities for people with moderate disabilities should be designed to recover more widely. In the future, education and psychological programs should be activated to overcome the symptoms of moderate disability and receive related information. Finally, disability awareness education should be further subdivided to bring about changes in the perception of disabilities.